Romanian Mothers’ Experiences Living With Diastasis Recti Abdominis - Klara KALMAN; Doriana CIOBANU; Theodora Florica URSU; Anca Maria DRAGAN (Romanian Journal of Physical Therapy)
Introduction: Diastasis recti abdominis (DRA) is characterized by deviation of the abdominal rectus muscle due to widening of the linea alba and laxity of the abdominal wall musculature and is a common condition affecting mothers both pre- and postnatally. Although DRA is gradually discovered as a common clinical problem, its management and prevention are still little known. Objectives: This study aims to assess current knowledge on DRA, its potential treatments and the awareness of this condition amongst women with DRA in Romania. The aim of this study was also to explore romanian mothers’ experiences living with DRA, how and when they found out they have DRA and who put the diagnosis, they have been or are in a recovery program and how they percept their condition affects quality of life. Subjects and methods: A narrative review was performed on the current literature by searching PubMed. The present study was undertaken from April to August 2024. Patients with DRA in Romania were questioned with an online survey, designed specifically for this study. In total 725 romanian women with diastasis recti abdominis completed the survey. Results: The literature search revealed contradictory results regarding the symptoms, clinical impact, and treatment of DRA. The majority of respondents, 52,1%, heard/learned about DRA only after 6 months after birth. The major source of information about DRA (68,5%) was the internet (Facebook, Youtube, search engines, mom groups) and friends; majority of women, 61,4%, self-diagnosed, tested themselves with the finger test; only 36,7% followed or are following a recovery program and from them only a half managed to close the DRA; 67,3% consider that their quality of life is affected moderate to very much by DRA. 89,5% believe that the gynecologist or the doctor who monitors the pregnancy should inform the expectant mother about DRA. Conclusions: More research is needed to establish appropriate educational interventions, which effectively increase knowledge about DRA among Romanian women. Assessment of DRA should be part of routine follow-up of postpartum women.